Thermal desalination via supercritical CO2 Brayton cycle: Optimal system design and techno-economic analysis without reduction in cycle efficiency. (April 2019) - Sharan, Prashant; Neises, Ty; Turchi, Craig
Highlights: Cogeneration (distillate + power) without reduction in the power plant efficiency. Proposed a methodology to maximize the waste heat recovery. New MED configuration to maximize the distillate production. Desalinated water cost is 17.8% cheaper compared to reverse osmosis. Abstract: The supercritical carbon dioxide (sCO2 ) Brayton cycle is an upcoming power cycle potentially providing higher energy efficiency and more compact turbomachinery compared to traditionally used Brayton and Rankine cycles. The heat rejected from the sCO2 Brayton cycle is quite hot (>70 °C) and must be cooled before flowing back to the compressor. However, this heat is ideal for producing fresh water with a thermal desalination system. This paper focuses on integrating multi-effect distillation (MED) with the sCO2 stream exiting the recuperator. A new methodology for integration of MED with the sCO2 Brayton cycle is proposed for simultaneous production of power and fresh water. The distillate produced does not affect the sCO2 cycle efficiency, i.e., distillate is produced without being a parasitic load to the power plant compared to conventional integration of MED with steam Rankine cycle. To maximize the energy recovery from the waste heat stream exiting the sCO2 cycle, a new methodology is formulated and discussed in the Appendix. Integration of MED with a 115 MWe sCO2 power plant (49.2% efficient) produces 2813 m 3 /day of distillate and the cost of distilled water is 1.1 /m 3 . Further, to enhance the distillate production, an innovative MED configuration is proposed, and for the same cycle operating condition with an electrical output 115 MWe, the net distillate production increases by 59% to 4472 m 3 /day at 1 /m 3 . The cost of desalinated water for the integrated system is 17.8% lower than that of a standalone reverse-osmosis plant having the same capacity. Parametric analysis is performed to calculate the optimal design parameters for the integrated MED-sCO2 system.